Perilaku Impulse Buying Konsumen pada Produk Lifestyle dengan Pendekatan Theory Of Planned Behavior - Sugiyanto; Safhira Rahmasari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Increasing economic growth and development of the retail industry in Indonesia has strengthened competition among retail business players. Therefore, one way for companies to compete with other retail businesses is to understand the factors that trigger impulsive buying behavior. The purpose of this study is to determine the influence of the factors in the Theory of Planned Behavior, namely attitude toward behavior, subjective norm, and perceived behavioral control on impulse buying behavior, either directly or indirectly through impulse buying intention. The sampling method used is non-probability sampling, and the technique to be used is purposive sampling. Data analysis was conducted using Partial Least Square - Structural Equation Modeling (PLS-SEM) with a sample size of 165 respondents. The results of the study prove that attitude toward behavior, subjective norm, and perceived behavioral control influence impulse buying intention. Attitude toward behavior, subjective norm, and perceived behavioral control influence impulse buying behavior, either directly or through impulse buying intention. Additionally, impulse buying intention influences impulse buying behavior. This research contributes to companies in designing marketing strategies to shape consumers impulsive buying behavior. Keywords: Impulse Buying, Attitude Toward the Behavior, Subjective Norm dan Perceived Behavioral Control.